2013
DOI: 10.1021/ma400819a
|View full text |Cite
|
Sign up to set email alerts
|

Postpolymerization Modification of Poly(glycidyl methacrylate) Brushes: An XPS Depth-Profiling Study

Abstract: Surface-initiated polymerization represents a versatile strategy to modify a diverse range of materials with thin, functional polymer coatings. While in many cases the desired functional groups can be directly incorporated via (co)polymerization of the appropriate monomer(s), other functional groups are incompatible with the polymerization strategies that are commonly used to grow polymer brushes and can only be introduced by postpolymerization modification. Determining the local concentration and spatial dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(98 citation statements)
references
References 41 publications
(69 reference statements)
6
92
0
Order By: Relevance
“…This could be attributed to the thickness effect of the copolymer film and the reactivity differences between AMA and OEGMA. Recently, Klok and coworkers have demonstrated that BSA (MW: 66.5 kDa) immobilized on the topmost layer (within 10 nm) of the poly(glycidyl methacrylate) film, grafted from an initiator‐anchored surfaces by SI‐ATRP . This supported our observation in which 35 nm‐thick film exhibited a higher binding capability for streptavidin as compared with the 6 nm‐thick film.…”
Section: Resultssupporting
confidence: 88%
“…This could be attributed to the thickness effect of the copolymer film and the reactivity differences between AMA and OEGMA. Recently, Klok and coworkers have demonstrated that BSA (MW: 66.5 kDa) immobilized on the topmost layer (within 10 nm) of the poly(glycidyl methacrylate) film, grafted from an initiator‐anchored surfaces by SI‐ATRP . This supported our observation in which 35 nm‐thick film exhibited a higher binding capability for streptavidin as compared with the 6 nm‐thick film.…”
Section: Resultssupporting
confidence: 88%
“…The ring opening reaction between 1,6-diaminohexane and the epoxide moiety of GMA was used to generate amine-functionalized membranes. 39 A membrane sample was submerged in a 2 M aqueous solution of the diamine. The volume of the solution was selected such that a 10× molar excess of diamine, relative to the epoxide moieties within the membrane, was present.…”
Section: Methodsmentioning
confidence: 99%
“…Note that functionalization may occur just at the top of the polymer brush or be distributed throughout the layer. A recent depth profiling experiment using XPS looked at the profile of the modifying molecules throughout the thickness of the brush and found larger molecules only bound at the top surface of the GMA brush [173].…”
Section: Modification and Detection Of Biological Componentsmentioning
confidence: 99%